Model of lumbar spinal stenosis in the experiment - Perepechai, Oleg; Ivanov, Georgiy; Novikov, Nik; Fishchenko, Iakiv (Journal of Education, Health and Sport, 2015)
Perepechai O., Ivanov G., Novikov N., Fishchenko I. Model of lumbar spinal stenosis in the experiment. Journal of Education, Health and Sport. 2015;5(7):171-178. ISSN 2391-8306. DOI 10.5281/zenodo.19735 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A171-178 https://pbn.nauka.gov.pl/works/581310 http://dx.doi.org/10.5281/zenodo.19735 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 30.06.2015. MODEL OF LUMBAR SPINAL STENOSIS IN THE EXPERIMENT O. Perepechai1, G. Ivanov2, N. Novikov3, I. Fishchenko1 1State University “Institute of Traumatology and Orthopedics of NAMS of Ukraine”, Kiev, Ukraine 2State University “Professor M. Sitenko’s Institute of Spine and Joint Pathology of NAMS of Ukraine”, Kharkov, Ukraine 3Medical Academy named after S.I. Georgievsky of Vernadsky CFU Abstracts The description of an experimental model of lumbar spinal stenosis on 20 rats. The experiment was symmetrical dissection of arc plates to the inside thin cortical layer plates, and then dissection of the latter. The middle part of the arc with the spinous processes of the vertebrae is separated from the rest of the arc, and articular processes. The separated middle part of the arc with yellow ligament is shifted in the ventral direction, reducing the size of the cavity of the spinal canal and fix the contacting bone edges with bone cement. Degenerative changes of the nerve roots were evaluated histologically by endoneural and epineural changes using a 7-point scale of G. Byrond and others. In the studied group of animals 7 days after spinal canal stenosis simulations appeared degenerative changes of nerve fibers, but the degree is low, and there is virtually no endoneural inflammation. The epineurium determined expressed or gross changes, indicating epineural inflammatory processes. After 1 month. There appeared dystrophic and degenerative changes of nerve fibers of the overwhelming majority (over 75%). At a later date (3 months), endoneural change remained practically the same as in the 1th month after surgery, epineural violations were preserved, there were groups and single fibroblasts as a sign of epineural fibrosis, as well as portions of connective tissue neoplasms and hyalinosis. Keywords: lumbar spinal stenosis, an experimental model.